2020
DOI: 10.1097/nne.0000000000000938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Complex Case Study and High-Fidelity Simulation on Mechanical Ventilation on Knowledge and Clinical Judgment of Undergraduate Nursing Students

Abstract: Background: Improving nursing students' knowledge and clinical judgment related to mechanical ventilation (MV) is paramount, considering the heightened need for MV due to the current COVID-19 (coronavirus disease 2019) pandemic. High-fidelity simulation (HFS) provides students with real-life clinical experiences that they would rarely confront in clinical training, especially complex case scenarios (such as a patient needing MV). Purpose: This study assessed students' clinical knowledge and judgment after incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…Third, the hypothesis, "there would be differences in the clinical reasoning competency for mechanical ventilation nursing between the experimental group, to whom the mechanical ventilation nursing VR simulation program was applied, and the control group, " was supported. This result was consistent with that of a previous study on mechanical ventilation-related HFS for nursing students in the UK, wherein clinical decision-making was found to be significantly improved in students, along with an improvement in their critical thinking, noticing, interpreting, reflecting, and responding capabilities [31]. This study supported the results of a study by Salameh et al [31], which reported that given the increased need for mechanical ventilation due to the current COVID-19 pandemic, providing nursing students with situations requiring mechanical ventilation for patients allowed them to gain real-world clinical experiences that they had not faced before, which suggested that these experiences could be effective in improving nursing students' clinical reasoning competency.…”
Section: Discussionsupporting
confidence: 92%
“…Third, the hypothesis, "there would be differences in the clinical reasoning competency for mechanical ventilation nursing between the experimental group, to whom the mechanical ventilation nursing VR simulation program was applied, and the control group, " was supported. This result was consistent with that of a previous study on mechanical ventilation-related HFS for nursing students in the UK, wherein clinical decision-making was found to be significantly improved in students, along with an improvement in their critical thinking, noticing, interpreting, reflecting, and responding capabilities [31]. This study supported the results of a study by Salameh et al [31], which reported that given the increased need for mechanical ventilation due to the current COVID-19 pandemic, providing nursing students with situations requiring mechanical ventilation for patients allowed them to gain real-world clinical experiences that they had not faced before, which suggested that these experiences could be effective in improving nursing students' clinical reasoning competency.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Lindsey and Jenkins 8 found the same results. Also, the finding of a higher student clinical judgment level after a simulation was also found in a quasi-experimental study conducted by Salameh et al 13 who compared clinical judgment of Palestinian nursing students in emergency nursing including the aspects of noticing, interpreting, responding, and reflecting based on treatment and control groups. Moreover, the findings of the current study are supported by Konieczny 12 who compares the effect of low-fidelity and high-fidelity simulation experience on clinical judgment.…”
Section: Discussionsupporting
confidence: 56%
“…9,10 Moreover, HFS has the potential to enhance pediatric nursing education and improve confidence among nurses and other healthcare professionals. 11 Further, previous studies concluded that high fidelity has the capability to improve decision making, 7 clinical judgment, 12,13 and selfawareness and empathy. 14 These high-fidelity simulation laboratories demonstrate an efficient outlet for nurses to practice the competencies required to take care of complicated, highly critical cases; drill for emergency preparedness; or function collaboratively amongst a team of healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation refers to the creation of an environment that is close to real‐life activities presented through computer software, role‐playing, case discussions or games, in which students can actively participate in learning discussions in a life‐like situation (Cheung et al, 2019; Fogg et al, 2020; Salameh et al, 2021). Simulation‐based situated learning can arrange different clinical situations according to the expected learning objectives so that students can experience practical problems they could encounter in hospitals, and actively learn knowledge, skills and attitudes to deal with clinical situations (So et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have indicated that skills learned through repeated practice in medical simulations are retained, and effectively improve the learners' medical skills (Offiah et al, 2019; Padilha et al, 2019). Moreover, medical simulation helps develop students' clinical judgement, critical thinking, problem solving and inferring skills (Fogg et al, 2020; Salameh et al, 2021). Previous studies showed that students have robust self‐efficacy after conducting medical simulation (Olsen et al, 2018; Su et al, 2019; Yamamoto et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%